A new species of Leiosaurus (Iguania: Leiosauridae) from central-western Argentina - Laspiur, Alejandro; Acosta, Juan Carlos; Abdala, Cristian S. (Zootaxa, 2007)
In this paper we describe a new species of the Leiosaurus genus from central-western Argentina. This new taxon presents remarkable differences regarding the lepidosis and coloration pattern compared to the other species of the genus: L. catamarcensis, L. paronae and L. bellii. The dorsal coloration pattern is unique and is characterized by dorsal markings similar to the colour design of some felines like the jaguar. This new species inhabits the highlands of central-western Argentina where steppe bunch grasses with low plant formation and low spiny shrubs prevail. However, little is known of its biology as with the other species of the genus Leiosaurus. The discovery of this new taxon is significant, because it has been one hundred years since the last description of a new species of these taxa.